Pelatihan Pembuatan Virgin Coconut Oil (VCO) Untuk Meningkatkan Nilai Jual Produk Olahan Kelapa Di Desa Curug Goong, Kabupaten Serang, Banten - Ruspita, Roza; Agipa, Ade Irmadiki (Universitas Muhammadiyah Malang, 2023)
Training on making Virgin Coconut Oil (VCO) has been held in Curug Goong Village, Serang Regency, Banten. VCO is pure coconut oil which has many benefits with a relatively easy manufacturing process. Curug Goong Village has potential as a producer of coconuts but has not been used optimally, so this activity aims to train the community to be able to process coconuts into products with a higher selling value. The training on making VCO was attended by 30 participants consisting of coconut farmers and housewives. This training was carried out in 3 stages of activity, these are: the preparation, the implementation and the evaluation stage. This training received a positive response from the people of Curug Goong Village. The evaluation results show 31 participants took part in socialization and training, 26 participants filled out questionnaires. After the training, the people of Curug Goong Village became more familiar with VCO, could differentiate between ordinary coconut oil and VCO, and could practice it at home.